Repair or replacement for isolated tricuspid valve pathology?: insights from a surgical analysis on long-term survival - Farag, Mina; Arif, Rawa; Ruhparwar, Arjang; Schmack, Bastian; Szabó, Gábor; Karck, Matthias; Weymann, Alexander (Medical science monitor, 2017)
Long-term follow-up data concerning isolated tricuspid valve pathology after replacement or reconstruction is limited. Current American Heart Association guidelines equally recommend repair and replacement when surgical intervention is indicated. Our aim was to investigate and compare operative mortality and long-term survival in patients undergoing isolated tricuspid valve repair surgery versus replacement.